Anniversaries in history of morphology in 2015 - S. A. Kutya (Морфологія, 2015)
500 years ago Pedro X (G) imeno (Pedro J (G) imeno, about 1515-1555 according to other data of 1577) was born - a Spanish anatomist, disciple and follower of Andrei Vesalius. He headed the chair of anatomy in Valencia and Alcalá. The first in Spain began to teach anatomy according to the method of his teacher.